2022
DOI: 10.22438/jeb/43/1/mrn-2003
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal variation in plant community, population structure and carbon stock of Quercus semecarpifolia Sm. forest in Kumaun Himalaya

Abstract: Aim: To study the impact of altitudinal variation on plant community composition, structure, dispersion and regeneration status of Quercus semecarpifolia forest in Kumaun Himalaya. Methodology: Along the altitudinal gradient, the forest stands between 2400 and 2610 m asl were selected at low, mid and high altitude. The phyto-sociological analysis was carried by laying ten quadrats of 10m × 10m at each site. Soil samples were collected with the help of soil corer from two depths. Various ecological indices and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…They found that increasing altitude is inversely proportional to the number of tree species. Q. semecarpifolia was the dominant tree species at all the studied sites; however, the absence of seedlings indicated no regeneration or poor regeneration of the seeds (Fartyal et al, 2022). In the Q. semecarpifolia-dominated forests, tree species richness ranges between 5 and 23 species, sapling richness from 4 to 14, species and seedling richness from 6 to 16 species Rawat et al, 2015).…”
Section: Climate and Soilmentioning
confidence: 90%
See 2 more Smart Citations
“…They found that increasing altitude is inversely proportional to the number of tree species. Q. semecarpifolia was the dominant tree species at all the studied sites; however, the absence of seedlings indicated no regeneration or poor regeneration of the seeds (Fartyal et al, 2022). In the Q. semecarpifolia-dominated forests, tree species richness ranges between 5 and 23 species, sapling richness from 4 to 14, species and seedling richness from 6 to 16 species Rawat et al, 2015).…”
Section: Climate and Soilmentioning
confidence: 90%
“…Soil organic carbon, soil total nitrogen, and the ratio of carbon and nitrogen are very important parameters to understand the biogeochemical cycles in the ecosystem, but still, it is poorly studied and understood (Yang et al, 2010). Fartyal et al (2022) reported that variation in species richness, distribution pattern, and regeneration potential is related to site characteristics, which is a very important aspect to check the ecosystem imbalance.…”
Section: Climate and Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the accurate identification of C. oblonga , we undertook a detailed community survey using 20 quadrats measuring 5 m × 5 m in August 2021. This quadrat size has been previously applied in surveys of shrub communities (Fartyal et al, 2022; Malakar & Joshi, 2020; Wang et al, 2020). Within each quadrat, clumped shrubs with an average height of 1.73 m (maximum height = 3.9 m) were the dominant species in the community.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has substantially declined worldwide as a consequence of rapidly changing climate and land uses (Newbold et al, 2015). In forest ecosystems, plant species diversity mitigates the competition between species by partitioning resources (light, nutrients, and water), thereby promoting biomass production, carbon accumulation, and ecosystem stability (Awasthi, Bargali, Bargali, Khatri, & Jhariya, 2022; Fartyal et al, 2022; Wang, Zhao, et al, 2019; Zhang et al, 2017). Moreover, plant species diversity can reduce the variability of ecosystem productivity in a fluctuating environment through compensatory effects (Awasthi, Bargali, Bargali, & Jhariya, 2022).…”
Section: Introductionmentioning
confidence: 99%